Right ventricular reverse remodeling after mitral valve transcatheter edge-to-edge repair. (3rd October 2022) - Stolz, L; Weckbach, L; Doldi, P; Orban, M; Braun, D; Stocker, T; Higuchi, S; Orban, M; Wild, M; Massberg, S; Hagl, C; Naebauer, M; et al.
Abstract: Background: Right ventricular dysfunction (RVD) is an important predictor for outcome in patients undergoing transcatheter mitral or tricuspid valve edge-to-edge repair (M/T-TEER). Due to the unique anatomy and contraction pattern of the RV, three-dimensional echocardiography (3DE) has emerged as a valuable tool in the assessment of RV function. While 3DE data showed RV reverse remodeling (RVRR) following T-TEER, respective data are absent in the setting of M-TEER. Purpose: We sought to assess RVRR after M-TEER using 3DE comparing baseline and follow-up RV measurements. Methods: Patients undergoing M-TEER treatment for relevant MR between August 2016 and February 2021 with eligible transthoracic 3DE of the RV at baseline and follow-up were included in the study. 3DE comprised RV end-diastolic and end-systolic volumes (RVEDV3D, RVESV3D), total RV stroke volume (RVSV3D) and RV ejection fraction (RVEF3D). Further, RV length (RVL3D) as well as RV basal (RVbase3D) and mid-ventricular diameters (RVmid3D) were derived from 3DE. RVRR was assessed as change in the respective 3DE parameters of RV dimensions between baseline and follow-up. Results: A total of 66 patients (45.5% female; age 78.5±8.2 years; EuroScore II 4.6±3.6%) were included in the study. From baseline to latest available follow-up (median interval 364 days, interquartile range 180–728 days), a significant reduction of RVEDV3D and RVESV3D was observed (RVEDV3D 140.2±50.2 ml to 128.1±46.1 ml, p<0.01 and RVESV3D 93.1±37.8ml to 87.1±34.7ml, p=0.04). The decrease in 3D-derived linear RV dimensions primarily occurred in the septolateral direction, while RV length did not change significantly. The observed RVRR was associated with significant reduction of TR severity. Of note, patients with RVRR showed also left ventricular reverse remodeling (LVRR). Conclusion: M-TEER is an effective treatment option for patients with MR which leads to LVRR and RVRR. Funding Acknowledgement: Type of funding sources: None.